Influence of foliar spray with some calcium sources on flowering, fruit set, yield and fruit quality of olive Kalmata and Manzanillo cultivars under salt stress - El-Hady, Eman S. (2023)
The results revealed that there were significant differences with calcium source treatment regarding number of inflorescences/shoot, no. of total flowers/inflorescences, sex expression, initial fruit set, final fruit set (%) and yield/kg (tree) and decreasing fruit drop (%) of olive oil Kalmata and Manzanillo cultivars compared with unsprayed in both seasons.